Impact of temperature variation on noise parameters and HCI degradation of Recessed Source/Drain Junctionless Gate All Around MOSFETs. (April 2023) - Kumar, Alok; Gupta, Tarun Kumar; Shrivastava, Bhavana P.; Gupta, Abhinav
Abstract: With the continuous scaling for MOS device, the noise parameters has becoming a critical parameter. The noise performance of an electronic device can be measured with the help of Minimum Noise Figure (MNF), Auto-Correlation Factor (ACF), Cross-Correlation Factor (CCF), and Output Impedance (Real Z 0 ). In this article, we have investigated the effects of temperature fluctuation on the noise parameter performance, and the Hot-Carrier Injection (HCI) degradation of the device Recessed Source/Drain Junctionless Gate All Around (Re-S/D-JL-GAA) and Junctionless Gate All Around (JL-GAA) MOSFETs. The comparative analysis presents that the temperature difference has the minimum impact on all noise characteristics. In this paper, the temperature variations from 200 K to 500 K have been studied to study the noise performance of the device at both low and high temperature applications. The simulation results confirm that all noise parameters are minimum in Re-S/D-JL-GAA compared to JL-GAA MOSFET. As a result, the Re-S/D-JL-GAA MOSFET is better alternative for analog circuits with low noise applications over a wider temperature range.